Implementasi Model Pembelajaran Discovery Learning pada Materi Sistem Gerak pada Tumbuhan di Kelas VIII SMP Negeri 5 Metro - Budiarti, Budiarti (Fakultas Tarbiyah dan Ilmu Keguruan UIN Jurai Siwo, Lampung, 2023)
Following studyingprocess is tedious for a lot of students, when it is not bemanaged properly and professionally. Therefore, a teacher is required to design and plan the studying program in a systematic, varietive and innovative way.. Through Classroom Action Research, for Class VIII.5 Science’s teacher in the material